Genetically detoxified pertussis toxin induces superior antigen specific CD4 T cell responses compared to chemically detoxified pertussis toxin - Naveen Surendran; Michael Pichichero (Taylor & Francis Group, 2019)
Pertussis is resurgent worldwide. Currently available acellular pertussis vaccines contain chemically detoxified pertussis toxin (PTc); a highly immunogenic genetically detoxified pertussis toxin (PTg) vaccine has been off the market for over a decade. We compared CD4+ T cell and B cell responses induced by genetically detoxified pertussis toxin (PTg) and chemically detoxified pertussis toxin (PTc) using naive human neonatal cells. Responses to novel adjuvants were also assessed. PTg induced significant antigen-specific CD4+ T cell activation and IL17 secretion than PTc. TLR agonist combinations improved PTg induced T cell-CD69 expression and IL17 secretion.